2020
DOI: 10.1016/j.midw.2020.102735
|View full text |Cite
|
Sign up to set email alerts
|

‘The rollercoaster’: A qualitative study of midwifery students’ experiences affecting their mental wellbeing

Abstract: Some members of the research team had pastoral responsibilities for the student cohort from which participants were drawn. They had no role in recruitment, direct contact with research participants and did not see unanonymised versions of the study transcripts. 2, Ethical approvalThe study was approved by the Research Ethics Committee of King's College London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Pre-pandemic research showed that pre-existing mental health problems of students are associated with experiencing emotional problems during education [50] , [51] . Based on the students’ self-report of pre-pandemic emotional health problems, it can be assumed these intensified or reoccurred during COVID-19 [12] , highlighting the importance of offering services to support the emotional wellbeing of midwifery students [17] , [51] , especially those with a history of/ pre-existing problem. A history of psychological problems played a significant role during the whole period of the study, while being single was only of influence on depression during the second measurement (T2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-pandemic research showed that pre-existing mental health problems of students are associated with experiencing emotional problems during education [50] , [51] . Based on the students’ self-report of pre-pandemic emotional health problems, it can be assumed these intensified or reoccurred during COVID-19 [12] , highlighting the importance of offering services to support the emotional wellbeing of midwifery students [17] , [51] , especially those with a history of/ pre-existing problem. A history of psychological problems played a significant role during the whole period of the study, while being single was only of influence on depression during the second measurement (T2).…”
Section: Discussionmentioning
confidence: 99%
“…There were serious concerns about the pre-COVID mental health of student midwives because assessment of emotional health indicated that student midwives’ emotional wellbeing was not optimal [15] . Midwifery education is recognised as being stressful with the (emotional) demands of the theoretical and practical components of the study, including clinical, academic, and financial challenges [15] , [16] , [17] . Younger midwifery students [18] and students who juggle their study with other commitments, such as a job, social activities, and family life, struggle more to keep up with their academic and clinical demands and their personal commitments [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Field notes were taken during the interview. The content analysis method was used to collate and analyze the data [3]. The study was approved by the institutional review committee at the fourth affiliated hospital of China medical university, Shenyang, Liaoning, China (EC-2019-KS-057).…”
Section: To the Editormentioning
confidence: 99%
“…Third, what role can mental health education play in moral education [7][8]. Academics have paid more attention to and studied mental health education as the fourth sub-system of ideological and political education, but the research on the essential attribute of mental health education's moral education function is still insufficient, and existing studies have either analyzed and listed the relationship between mental health education and its relationship in a general sense from the perspective of the discipline of moral education [9][10][11]. Alternatively, they have explored the issue from the perspective of moral education from top to bottom and from the outside to the inside and put forward the requirements for mental health education [12][13].…”
Section: Introductionmentioning
confidence: 99%